Nigerian English and the Phonotactic Influence of the West Chadic Languages - Blessing Saina’an Lagan; Mary Daniel Nimram (Universal Journal of Educational Research)
Phonotactics is a fundamental aspect of phonology that governs the permissible combinations of sounds in a given language. It consists of rules that dictate how phonemes; the smallest units of sound can be arranged to form syllables and words. These rules determine which sound sequences are allowed and which are prohibited, shaping the phonological structure of a language. This study examines the phonological constraints of four West Chadic languages in Nigeria (Piapung, Mwaghavul, Goemai and Kwagalak) and observes how the phonotactic features of these languages influence the English pronunciation of the native speakers by using the theory of Second Language Acquisition (SLA) and phonological interference or language transfer. Words and sentences with phonotactic constraints were given to 40 participants to read (10 from each language). The research identified areas where these features create pronunciation challenges and the possible implications for pedagogy. The findings of the research show that speakers move between L1 and L2 norms, producing an intermediate phonological system. It concludes by suggesting some teaching strategies that can help speakers overcome their pronunciation challenges and pedagogy.